2022
DOI: 10.3233/jad-215067
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Common Variants of APOE, ABCA7, A2M, BACE1, and Cerebrospinal Fluid Biomarkers in Alzheimer’s Disease: Data from the PUMCH Dementia Cohort

Abstract: Background: The previous studies have identified several genes in relation to Alzheimer’s disease (AD), such as ABCA7, CR1, etc. A few studies have explored the association between the common variants, mainly in the non-coding regions of these genes, and cerebrospinal fluid (CSF) biomarkers. Fewer studies target the variants in the coding regions. Objective: To illustrate the association between the common variants within or adjacent to the coding regions of AD susceptible genes and CSF biomarkers in AD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The current analysis corresponds to a similar examination of genes associated with AD and their variants, as summarized in earlier studies [19]. The present study also corroborated the association between AD and its comorbid diseases such as dementia, Parkinson's disease, and type 2 diabetes, as documented earlier [20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…The current analysis corresponds to a similar examination of genes associated with AD and their variants, as summarized in earlier studies [19]. The present study also corroborated the association between AD and its comorbid diseases such as dementia, Parkinson's disease, and type 2 diabetes, as documented earlier [20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…Shortly, multiple genetic markers were associated with increased amyloid pathology, which has been replicated in several studies, 38,51–54 which could be indicative for a role of ABCA7 dysfunction in the amyloid pathway. Evidence for association with tau pathology has been more inconsistent 38,51,54,55 . Studies in different brain regions generally suggested association of risk alleles with either brain atrophy or altered functional connectivity 38,56–59 .…”
Section: Abca7 Ad‐associated Variantsmentioning
confidence: 83%
“…The abovementioned GWAS sentinel SNPs have also been studied for their association with AD endophenotypes, such as amyloid deposition, tau pathology, brain morphology, and various clinical symptoms, which has been extensively reviewed before 38,50 . Shortly, multiple genetic markers were associated with increased amyloid pathology, which has been replicated in several studies, 38,51–54 which could be indicative for a role of ABCA7 dysfunction in the amyloid pathway. Evidence for association with tau pathology has been more inconsistent 38,51,54,55 .…”
Section: Abca7 Ad‐associated Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, A2M is markedly elevated in neuronal protrusions in senile plaques, neurofibrillary tangles, and atrophic neurons in Alzheimer’s disease patients’ brains ( 23 ). A2M is strongly associated with neurological disorders associated with dopaminergic neuronal dysfunction and cerebrospinal fluid (CSF) biomarkers within the coding region of Alzheimer’s disease (AD) susceptibility genes ( 22 , 24 ). This study indicates that A2M, in the XXZ group of patients with acute ischemic stroke, is primarily associated with “inflammatory response” and “response to lipid.” Decreasing A2M expression may influence sICAS through anti-inflammatory and lipid responses and may also contribute to improving neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%